VD_FINDINFO HC / 2014 / 153 vom 9. Januar 2014 - VD Tribunal cantonal (2014)
DÉCISION DE RENVOI, CONTRAT D'ENTREPRISE, DÉFAUT CACHÉ, NORME SIA | 363 CO, 66 al. 1 OJ, 318 al. 1 let. c CPC (CH), 405 al. 1 CPC (CH)